Behavioural ecology of the sunda colugo Galeopterus variegatus (Mammalia : Dermoptera) in Bako National Park, Sarawak, Malaysia - Muhammad Dzulhelmi, Muhammad Nasir (Universiti Malaysia Sarawak (UNIMAS), 2011)
CA study on the behavioural ecology of the Sunda Colugo (Galeopterus variegatus) in Bako National Park headquarters was conducted between 16th August 2008 and 22d July 2009. The objectives of this study were to determine the roosting selection, diet preferences and behaviour patterns of the Sunda Colugo in its free ranging habitat. Visual daytime search and focal samplings technique was applied for this study. A total of 56 sightings of the Sunda Colugo found roosting on 32 selected trees comprising 10 species and nine families within the main study area. The Sunda Colugo have preferences for flex cymosa as its roosting tree species (Fisher's exact test: 0.705 > 0.05). A total of 12 species from 10 families were identified as the diets for the Sunda Colug) Interestingly, the Sunda Colugo with young (GY) have higher preferences for Buchanania arborescens. Furthermore, a total of ten main behaviour categories comprising 39 behaviour patterns have been catalogued from this observation. Only the Maintenance Pattern (Kruskal- Wallis test: H= 14.85, P=0.001) and grooming (Kruskal-Wallis test: H=1 1.84, P=0.003) differs significantly among the individual categories (GY, GN, ON). This database reveals potential studies which can be use to conserve this species especially in Bako National Park.